2005
DOI: 10.1097/01.ju.0000161210.17365.cc
|View full text |Cite
|
Sign up to set email alerts
|

FUNCTION OF THE LOWER URINARY TRACT IN MICE LACKING α 1d -ADRENOCEPTOR

Abstract: The results demonstrate that the alpha1d-AR subtype has an important role in regulating bladder function. They theoretically support a clinical finding that alpha1-blockers with significant affinity for alpha1d-AR are effective for treating storage symptoms associated with benign prostatic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 20 publications
2
61
0
1
Order By: Relevance
“…Urine volume was measured using the 48-h frequency/volume analysis system as previously described (4). Briefly, each mouse was placed in a metabolic cage connected to a digital scale and personal computer.…”
Section: Methodsmentioning
confidence: 99%
“…Urine volume was measured using the 48-h frequency/volume analysis system as previously described (4). Briefly, each mouse was placed in a metabolic cage connected to a digital scale and personal computer.…”
Section: Methodsmentioning
confidence: 99%
“…68,69 Studies in mice that lack the α 1D adrenergic receptor have indicated that there is an important role for these receptors in the regulation of bladder function. 70 The α 1D adrenergic receptor is expressed within the bladder urothelium, and it seems that tonic activation of urothelial α 1D receptors by catecholamines might be involved in bladder sensory mechanisms. 71 Catecholamines could be released from nerves adjacent to the urothelium or from nerves that innervate nearby blood vessels, as the suburothelial region receives a rich blood supply.…”
Section: Role Of Adrenergic Receptors In Bladder Outlet Obstructionmentioning
confidence: 99%
“…These differences in long-term outcomes also suggest a difference in the effect profile between naftopidil and tamsulosin. Although experimental models could explain the association of the lower urinary tract functions with α 1D -adrenoceptor modulations [Chen et al 2005], previous studies failed to give its clinical certification.…”
Section: After Approval Of Naftopidil For the Management Of Benign Prmentioning
confidence: 99%
“…However, naftopidil, which shows an affinity to the α 1D -subtype to a certain extent in addition to a high affinity to the α 1A -adrenoceptor, has also been used in clinical practice in limited nations [Takei et al 1999]. Although details of the physiological mechanism of the α 1D -adrenoceptor and the pharmacological effect of naftopidil are still unclear [Kojima et al 2009;Yamaguchi et al 1997], recent experimental studies have suggested a role played by the α 1D -adrenoceptor subtype in bladder function during the storage phase as well as the regulation of detrusor contractility [Malloy et al 1998;Chen et al 2005]. The present review systematically refers to and summarizes the published studies on naftopidil in clinical practice to specify the role of this unique agent in the management of BPH.…”
Section: Introductionmentioning
confidence: 99%